High hydrostatic pressure enhances the anti-proliferative properties of lotus bee pollen on the human prostate cancer PC-3 cells via increased metabolites. (28th October 2020) - Tuoheti, Tuhanguli; Rasheed, Hafiz Abdul; Meng, Ling; Dong, Ming sheng
Abstract: Ethnopharmacological relevance: The beneficial effects of bee pollen on prostate diseases are well known. Clinicians confirm that, in nonbacterial prostate diseases, bee pollen improves the condition of patients effectively. However, there is insufficient evidence to rate effectiveness of bee pollen on prostate cancer. Aim of the study: High hydrostatic pressure (HHP), an effective non-thermal technique to improve the nutritional quality and bio-functionality of plant-based foods, was used to increase the anti-proliferative properties of Lotus ( Nelumbo nucifera) bee pollen (LBP) in prostate cancer PC-3 cells via enhancement of bioactive compounds. Materials and methods: Freeze-dried lotus bee pollen produced from Fu Zhou city, Jiangxi province, China, was processed by high hydrostatic pressure (HHP). The anti-proliferative activities, apoptosis of ethanol and methanol extracts in prostate cancer PC-3 cells was evaluated using MTT method and Annexin-V/PI cell apoptosis assay kit, respectively. The changes of metabolites were determined using UPLC-Triple-TOF-MS analysis platform. Results: HHP treatment enhanced anti-proliferative activities, cell apoptosis, cell cycle disruption, glutathione-depletion in prostate cancer PC-3 cells. The metabolomics analysis showed that some metabolites such as chaetoglobosin A, glutathione oxidized, cyanidin 3-rutinoside, brassicoside, sophoranone, curcumin II, soyasaponin II were significantly increased (p < 0.05) after the HHP treatment, PCA results shown that these bioactive components have quite correlation with anti-proliferative activities of lotus bee pollen on the PC-3 cells. The results indicated that HHP enhances the anti-prostate cancer activity of lotus bee pollen via increased metabolites. Graphical abstract: Image 1